Rethinking the Eucharist in the aftermath of COVID-19 disruptions: A comparative study of Reformed and Pentecostal theology of sacraments - Mpofu, Buhle (HTS teologiese studies, 2021)
This contribution recommends a re-thinking of Christian traditions with regards to sacraments and use of technology in the context of the coronavirus disease 2019 (COVID-19) pandemic. It is a comparative study that employed field observations from two congregations with different traditions: one from Protestant Reformed tradition and another from Pentecostal Charismatic background to analyse how they conducted Holy Communion services. By highlighting positive aspects of COVID-19 disruptions on traditional practices, the study challenged traditional understanding of ‘sacred space’ and re-appropriates the virtual role of a priest as symbolic embodiment of the presence of Christ extended through virtual, audio and tele-visual presence. The contribution also demonstrated how ontological questions help us discern what separates the sacred from the secular and concluded that the transformative nature of the sacrament of the Holy Communion has a uniquely power-levelling role in communities.Contribution: This article contributes to conversations on the role of technology in sacraments within the Reformed Christian tradition and presents a systematic and practical reflection on the intersecting modes of sacramental practices within different Christian traditions.